The Effect of Product Quality, Competence, and Facilities on Customer Satisfaction: A Study at LS Studio Music Recording Bandung - Jerry Kristianto; Uce Karna Suganda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine how much influence product quality, competence, and facilities have on customer satisfaction at LS Studio Musik Bandung. The data source in this study uses primary sources, namely by distributing questionnaires via Google forms filled out by 116 respondents from LS Studio customers. All data processing and analysis are carried out using the Smart PLS application. The results of the study concluded based on the R square results of 0.841 which means that product quality, competence and facilities have an influence on customer satisfaction of 84.1% and the remaining 15.9% is influenced by other factors not studied, then based on the F square results it was found that the results of facilities on customer satisfaction have the largest effect size compared to product quality and technician competence with a value of 0.369> 0.35 and the results of the hypothesis test obtained the product quality variable has a t statistic value of 2.631> 1.96 with a p-value of 0.009 <0.05, it can be concluded partially that the product quality variable has a significant influence on customer satisfaction, the competence variable has a t statistic value of 2.584> 1.96 with a p-value of 0.010 <0.05, it can be concluded partially that the competence variable has a significant influence on customer satisfaction and the facility variable has a t statistic value of 5.006> 1.96 with a p-value of 0.000 <0.05, it can be concluded partially The facility variable has a significant influence on customer satisfaction.